Vozvrashchenie Budulaia - Blank, Alexander (Soviet Union : Gosteleradio SSSR, 1985)
The main hero, a gypsy named Budulai, was severely beaten up by bandits and lost his memory for half a year. By chance he meets his son Vania, who learned from his mother that his real father is Budulai. The appearance of the son makes Budulai's memory come back. The film is a sequal to a television series "Tsygan" (Gypsy), on 2 tapes.
Keywords: Fiction films